Biochemistry, genetics and regulation of bacilysin biosynthesis and its significance more than an antibiotic - Öğülür, İsmail (My University, 2016)
Bacillus subtilis has the capacity to produce more than two dozen bioactive compounds with an amazing variety of chemical structures. Among them, bacilysin is a non-ribosomally synthesized dipeptide antibiotic consisting of l-alanine residue at the N terminus and a non-proteinogenic amino acid, l-anticapsin, at the C terminus. In spite of its simple structure, it is active against a wide range of bacteria and fungi. As a potent antimicrobial agent, we briefly review the biochemistry and genetics as well as the regulation of bacilysin biosynthesis within the frame of peptide pheromones-based control of secondary activities. Biological functions of bacilysin in the producer B. subtilis beyond its antimicrobial activity as well as potential biotechnological use of the biosynthetic enzyme l-amino acid ligase (Lal) are also discussed. © 2015 Elsevier B.V.